Haematological alterations and molecular detection of theileriosis in crossbred cattle - BHANOT, VANDNA; GANGULY, ANITA; SHARMA, PARESH (The Indian Journal of Animal Sciences, 2019)
Theileriosis is a fatal haemoprotozoan disease which is a major threat to dairy and related industries. This study was undertaken to ascertain haematological changes and molecular diagnosis of Theileria annulata in crossbred cows. The infected group showed significantly lowered mean values of TEC, Hb, PCV and thrombocytes. Also the red blood cell (RBC) indices, viz. MCV, MCH, and MCHC were significantly lower indicating hypochromic microcytic anaemia. Out of 652 blood samples analysed by Giemsa stain, the overall prevalence of theileriosis was 36.3% during July 2015 to June 2017. Highest positivity of Theileriosis was noticed in summer (40.1%) followed by Spring/autumn (38.3%), rainy (34.3%) and lowest in winter (31.5%). About 48% blood samples were positive for Theileria annulata by 18SrRNA and TASP gene based PCR.